Plural Subject Theory and the Common Good: A Human Rights Critique in Dialogue with Islamic Political Thought - Sidra Tariq (Journal of Islamic Civilization and Culture Review, 2026)
This paper critically examines Margaret Gilbert's plural subject theory through the objective of human rights and the concept of the common good. Gilbert's plural subject theory offers a thrilling account of collective agency grounded in joint commitment, explaining how individuals form unified agents capable of coordinated action and shared responsibility. However, despite its analytical strength, the theory remains normatively limited in addressing the moral status of non-members and the principle of universal human equality. This study adopts a conceptual and normative philosophical methodology to develop a human rights-based critique of plural subject theory. It argues that while joint commitments smooth social cohesion and collective identity. They may also create exclusionary and oppressive outcomes when not in line with universal ethical principles. To address these limitations, the paper incorporates insights from Islamic political philosophy, particularly the concepts of maslahah (public welfare), adl (justice), shura (consultation), and ummah (community), to construct a more comprehensive and ethically grounded conception of the common good. By joining the plural subject theory with human rights and cross-civilizational ethical contexts, the study proposes a revised normative model of collective agency in which human rights are understood as collectively recognised moral obligations. This model provides a more comprehensive account of collective action united with universal human dignity and offers a stronger foundation for evaluating political, social, and institutional arrangements.